Preventing Early Marriage: The Role of Management Strategies of the Office of Religious Affairs in Panai Hulu District - Annisa Rohimah; Faridah (Institut Agama Islam Negeri (IAIN) Curup, 2026)
Purpose − This study aims to analyze how the management of the Office of Religious Affairs (KUA) addresses early marriage at the sub-district level. The study positions the KUA as a strategic actor that not only performs administrative functions but also plays an educational and preventive role based on religious values. Method − The research employs a descriptive qualitative approach using interviews, observations, and documentation, which are analyzed through stages of data reduction, data display, and conclusion drawing. Findings − The findings show that KUA management is implemented through the functions of planning, organizing, implementation, as well as monitoring and evaluation. Planning is carried out by identifying causal factors contextually; organizing is integrative without a specific structure but strengthened through cross-institutional collaboration; implementation is realized through premarital counseling in schools and religious forums involving both youth and parents; and monitoring is conducted through the observation of marriage and marriage dispensation data, as well as internal reflection. Overall, KUA management demonstrates an adaptive and collaborative approach in efforts to prevent early marriage, although it still faces limitations in terms of resources and evaluation systems.